A Single Case of Tourette's Syndrome Treated with Traditional Chinese Medicine - Min-Hwa Lee (Medical Association of Pharmacopuncture Institute, 2017)
The objective of this case study was to investigate the effectiveness of Chinese medicine in treating Tourette's syndrome. Tourette's syndrome is a childhood- onset disorder that is characterized by sudden, involuntary movements or tics. The participant in this study was a 33-year-old male who had been diagnosed with Tourette's syndrome at the age of 9 years. His major complaints included facial tics, shoulder shrugging, and clearing the throat. Using a combination of acupuncture, herbs, Gua-Sha, and lifestyle changes once a week for 35 treatments, all the symptoms were reduced by 70%, as reported by the patient. In this case, the results indicated that Chinese medicine was able to minimize the symptoms of Tourette's syndrome. Further investigation is needed to support this argument. Tourette's syndrome, which was first described in 1885 by a French physician named Gilles de la Tourette, is characterized by facial tics, involuntary body movements from the head to the extremities, or vocal tics, and it usually has its onset in childhood. It is a neuropsychiatric disorder. The treatment for Tourette's syndrome is based on pharmacological treatment, behavior treatment, and deep brain stimulation. Unfortunately, none of these could completely control the symptoms; furthermore, antipsychiatric drugs might cause additional side effects, such as Parkinson symptoms, tardive dyskinesia, and metabolic disturbances. Finding acupuncture and oriental medicine literature on treatment of Tourette's syndrome was difficult, especially that written in English. Some research papers that have been translated into English indicated that Chinese herbs and acupuncture could reduce the tics significantly. For example, a study by Dr Pao-Hua Lin reported the significant effects of using acupuncture and oriental medicine in treating 1000 Tourette's syndrome cases. This case was treated to further investigate the principles of Dr Lin's study.